The Influence of the Problem-Based Learning Model Assisted by Electronic Student Worksheets on the Science Learning Outcomes - Fahrur Rozi; Nirwana Anas; Eka Margareta Sinaga; Yusron Abda’u Ansya (Jurnal Penelitian Pendidikan IPA, 2025)
The problem of this research is the low natural science learning outcomes of elementary school students caused by student-centered learning and the inadequate use of teaching materials. This study aims to determine the effect of the problem-based learning model assisted by electronic student worksheets based on liveworksheet on natural science learning outcomes. This study uses a quantitative approach with a nonequivalent control group design. The research sample consists of fifth-grade students from SD Muhammadiyah 29 Sunggal. Data was collected through pretest and posttest, and analyzed using normality test, homogeneity test, and hypothesis test through Independent Samples t-test. The results show that the average posttest score of the experimental class was 86.08, higher than the control class at 76.33. The t-test resulted in a significant value of p < 0.001 with a mean difference of -9.747 and a 95% confidence interval (-14.095 to -5.398), indicating a significant difference. Based on the data analysis results, it is stated that the problem-based learning model assisted by electronic student worksheets has an impact on improving the learning outcomes of 5th-grade elementary school students in science learning. These findings support the development of student-centered science education aligned with the Merdeka Curriculum